The Use of Powerpoint-Based Interactive Plywood Gamelan in Learning Local Sound Art in Elementary Schools - Binti Muflikah; Vica Ananta Kusuma; Abdul Aman (Journal of Innovation in Educational and Cultural Research, 2022)
Students' low interest and learning achievement towards the Local Sound Art is the main problem in this study. As a step to improve learning, classroom action research was conducted. The purpose of this study is to describe students' interest and achievement in Local Sound Art after applying Interactive plywood gamelan based on PowerPoint to elementary school students. The research applied classroom action research methods. The steps taken are by carrying out the learning cycle I to cycle II. Students learn each material interactively in PowerPoint until they arrive at the gamelan playing menu. The menu will be connected to plywood gamelan, which guides students to play the notes in the macapat and dolanan songs independently. The PowerPoint-based plywood gamelan media is proven to increase students' interest and learning achievement. Data from research used observational data and assessment data of song material. The student activity was increased from the early stages. The number of good categories was eight students (40%) and fewer categories 12 students (60%). This research concludes that PowerPoint-based interactive plywood gamelan is effective in learning local sound arts in elementary schools because students' interests and learning outcomes are on average completed.